Characterization, Kinetics And Equilibrium Studies Of Paracetamol Adsorption On The Oil Palm Fronds (Opf) Cellulose Nanocrystals - Idris, Nor Najhan (2022)
Pollution of water via pharmaceutical drugs such as paracetamol have been a highly concerning issue; and effective measures must be taken to treat these aquatic contaminants. Hence, the present study explored use of cellulose nanocrystals (CNC) isolated from oil palm fronds (OPF) through pre-treatments and acid hydrolysis as an environmental friendly adsorbent. The complementary analyses showed that the OPF CNC possesses a crystallinity index of 43.60 %, surface area (10.51 m2 g-1), and an aspect ratio of 19.98. Besides, the OPF CNC and OPF CNC-AC hydrogel beads have been successfully produced, optimised, and applied for paracetamol removal. The modification of OPF CNC-AC hydrogel beads with the commercial activated carbon (AC) has improved the BET surface area up to 85.19 m2 g-1. The adsorption studies of paracetamol onto OPF CNC and OPF CNC-AC hydrogel beads can be achieved at 60 g and 0.6 g of adsorbent dosage, respectively, at a pH 3 with a contact time of 170 min under room temperature. It was observed that the produced data fitted best with the pseudo-second order kinetic model and Freundlich isotherm model for characterising the adsorption of paracetamol onto OPF CNC hydrogel beads with a maximum adsorption capacity, qmax of 0.03 mg g-1. Meanwhile, for OPF CNC-AC hydrogel beads, the pseudo-second order kinetic model and Langmuir isotherm model showed the best correlation for the adsorption of paracetamol with a qmax value of 21.31 mg g-1. Therefore, the output from this study may suggest that OPF CNC and OPF CNC- xxiv AC hydrogel beads can be used as natural adsorbents for the removal of paracetamol waste.